The happy hippopotami - Martin, Bill.; Everitt, Betsy (San Diego : Harcourt Brace, 1991)
The happy hippopotami enjoy a merry holiday at the beach, wearing pretty beach pajamas, dancing the maypole, or battling with water guns.
"Voyager Books."
NP
Keywords: Hippopotamus -- Fiction; Beaches -- Fiction; Stories in rhyme; Hippopotamus -- Fiction; Beaches -- Fiction; Stories in rhyme